2021
DOI: 10.1017/s026646742100016x
|View full text |Cite
|
Sign up to set email alerts
|

Freeze tolerance in neotropical frogs: an intrageneric comparison using Pristimantis species of high elevation and medium elevation

Abstract: Paramos are high-elevation tropical Andean ecosystems above the tree line that display variable temperature and frequent freezing spells. Because a significant anuran community lives in this environment, physiological protection against freezing must characterise individuals in this community. Antifreeze protection has been studied in amphibians from other communities, and it is likely that Paramo anurans rely on the same underlying molecules that convey such protection to Nearctic species. However, given the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 44 publications
0
3
0
Order By: Relevance
“…Specifically, we found that glucose appears in our top models and exhibits a positive relationship with elevation, which supports our prediction and suggests glucose may be an acclimation response to cold temperatures at high elevation. High glucose levels have been observed in other species of terrestrial, neotropical frogs found at high elevations (Carvajalino-Fernández et al, 2021), a trait indicative of freeze-tolerance in anurans (Storey, 1997). Furthermore, glucose may be important in helping coqui at high elevations meet energetic demands under suboptimal temperatures.…”
Section: Discussionmentioning
confidence: 96%
See 2 more Smart Citations
“…Specifically, we found that glucose appears in our top models and exhibits a positive relationship with elevation, which supports our prediction and suggests glucose may be an acclimation response to cold temperatures at high elevation. High glucose levels have been observed in other species of terrestrial, neotropical frogs found at high elevations (Carvajalino-Fernández et al, 2021), a trait indicative of freeze-tolerance in anurans (Storey, 1997). Furthermore, glucose may be important in helping coqui at high elevations meet energetic demands under suboptimal temperatures.…”
Section: Discussionmentioning
confidence: 96%
“…Given that an animal's physiology allows them to respond to environmental challenges, the coqui may be experiencing temperature‐mediated changes to baseline physiological traits as it invades higher elevations. For instance, other neotropical terrestrial frogs exhibit an increase in their blood glucose levels (an energy metabolite), which serves as a cryoprotectant in response to lower temperatures at high elevations (Carvajalino‐Fernández et al, 2021). Temperature can also influence the oxidative stress of ectotherms tied to elevated metabolism (Bury et al, 2018; Reguera et al, 2014; Souri & Rastegar‐Pouyani, 2018), which increases the demand for energy metabolites (French et al, 2021; Webb et al, 2019).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation